PANoptosis as a Two-Edged Sword in Colorectal Cancer: A Pathogenic Mechanism and Therapeutic Opportunity - Györgyi Műzes; Ferenc Sipos (Cells)
The examination of PANoptosis in colorectal cancer is particularly important, as many tumor cells can evade apoptotic cell death while continuing to proliferate through inflammatory mediators and creating an immunosuppressive environment. The PANoptosome functions as a regulatory complex that unites proteins governing pyroptotic, apoptotic, and necroptotic pathways, rather than allowing distinct death pathways to compete. The expression and functional status of key molecules within the PANoptosome, such as ZBP1, RIPK1, RIPK3, CASP8, and ASC, may influence tumor viability and immune detection. The tumorigenic impact of PANoptosis is complex and predominantly manifests through chronic inflammation, immune response modulation, and changes in the tumor microenvironment. PANoptosis also aids in the defense against colon cancer by directly eradicating tumor cells and modifying the cellular environment. The expression profile of PANoptosis components may possess prognostic and predictive significance. The therapeutic ramifications of PANoptosis in colorectal cancer are now being investigated through many avenues. It provides an opportunity to develop targeted therapeutic techniques. In contrast, it may also be pertinent in conjunction with immunotherapy, as PANoptosis signifies an immunogenic type of cell death and may consequently enhance the anti-tumor immune response. A thorough comprehension of how these parameters influence PANoptosis is crucial for practical implementation.